2017
DOI: 10.1111/jan.13507
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing nurse‐assessed quality nursing care: A cross‐sectional study in hospitals

Abstract: This study shows how work environment past burnout and job satisfaction influences quality nursing care. Apart from nurses' work conditions of work environment and patient-to-nurse ratio, hospital administrators should pay more attention to nurse outcomes of job satisfaction and burnout when designing intervention programmes to improve quality nursing care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
78
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 45 publications
5
78
0
4
Order By: Relevance
“…Laschinger, Borgogni, Consiglio, and Read () found that when nurses experience the syndrome of burnout, it can significantly influence their physical, psychological and mental health in negative terms. Additionally, when nurses are exposed to a high rate of burnout, it can lead to several negative outcomes for healthcare organisations (Adriaenssens, De Gucht, & Maes, ), such as reduced quality of nursing care (Liu & Aungsuroch, ), an increased expressed intention to leave (Chang et al, ), absenteeism (Suñer‐Soler et al, ) and alarmingly compromised patient safety (Baier, Roth, Felgner, & Henschke, ). Maslach () stated that burnout is an event that results from cumulative effects in stressful workplaces.…”
Section: Introductionmentioning
confidence: 99%
“…Laschinger, Borgogni, Consiglio, and Read () found that when nurses experience the syndrome of burnout, it can significantly influence their physical, psychological and mental health in negative terms. Additionally, when nurses are exposed to a high rate of burnout, it can lead to several negative outcomes for healthcare organisations (Adriaenssens, De Gucht, & Maes, ), such as reduced quality of nursing care (Liu & Aungsuroch, ), an increased expressed intention to leave (Chang et al, ), absenteeism (Suñer‐Soler et al, ) and alarmingly compromised patient safety (Baier, Roth, Felgner, & Henschke, ). Maslach () stated that burnout is an event that results from cumulative effects in stressful workplaces.…”
Section: Introductionmentioning
confidence: 99%
“…Although the association of work environment with work attitude has been widely investigated in hospital nurses, the underlying mechanism of this relationship has been less explored. A few researchers have examined the mediating role of psychological characteristics, such as resilience, work engagement and psychological well‐being, on the associations between work environment and work attitudes (Liu & Aungsuroch, ; Pahlevan Sharif, Ahadzadeh, & Sharif Nia, ). Additional mediators should be explored to explain how work environment influences work attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, the influence of NJS on patient and nurse outcomes is well-documented (Choi & Kim 2016). Evidence reveals greater NJS is associated with better quality of care (Liu & Aungsuroch 2018), and improved retention and intention to retain work (Masum et al 2016). In the Middle East, several researchers examined NJS.…”
Section: Introductionmentioning
confidence: 99%